The effect of nutritional risk management program on the growth and development of infants and toddlers with congenital heart disease after discharge - Huang, Ya-Li; Luo, Wen-Yi; Wang, Xie-Lei; Zheng, Feng; Gao, Jian-Hua; Chen, Ming-Xia; Pan, Yang-Dong (Frontiers in Pediatrics, 2024)
Objective: To evaluate the effect of nutritional risk management program on the growth and development of infants and toddlers with congenital heart disease(CHD) after discharge. Methods: Infants and toddlers with CHD discharged from a children's specialized hospital in southeast China were selected as the research subjects. The subjects were divided into the intervention group and the control group. The intervention group underwent a nutritional risk management program combined with traditional follow-up after discharge, whereas the control group received traditional follow-up after discharge. The primary outcome measure were the height-for-age Z-score (HAZ), weight-for-age Z-score (WAZ), and weight-for-height Z-score (WHZ) at different time point and the percentage of growth and development curves were also recorded and analyzed. Results: There were no statistically significant differences in general characteristics between the two groups. However, in the intervention group, the percentages of HAZ<-2, WAZ<-2, and WHZ<-2 were lower than those in the control group at 3rd and 6th months after discharge (P<0.05). The percentage of growth and development curves (3%-97%) was higher than that in the control group (P>0.05). The readmission rate within 6 months after discharge in the intervention group was lower than that in the control group (P<0.05). Conclusion:Implementing nutritional risk management program for infants and toddlers with CHD after discharge can help improve postoperative malnutrition, promote growth and development and achieve catch-up growth as soon as possible.